2018
DOI: 10.1038/s41467-017-02655-1
|View full text |Cite
|
Sign up to set email alerts
|

Active and dynamic mitochondrial S-depalmitoylation revealed by targeted fluorescent probes

Abstract: The reversible modification of cysteine residues by thioester formation with palmitate (S-palmitoylation) is an abundant lipid post-translational modification (PTM) in mammalian systems. S-palmitoylation has been observed on mitochondrial proteins, providing an intriguing potential connection between metabolic lipids and mitochondrial regulation. However, it is unknown whether and/or how mitochondrial S-palmitoylation is regulated. Here we report the development of mitoDPPs, targeted fluorescent probes that me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 63 publications
4
84
0
1
Order By: Relevance
“…APT1 and APT2 were reported, and widely accepted, to display a cytosolic localization with preferred membrane association to the Golgi apparatus and the plasma membrane based on overexpression of fusion proteins using myc-FLAG (Kong et al 2013) or mCitrine (Vartak et al 2014) tags. We have, however, recently found that endogenous APT1 or APT1 overexpressed as a fusion to small tags localize primarily (although not exclusively) to mitochondria, whereas overexpression of APT1 using a bulky tag such as mCitrine prevents it from accumulating in mitochondria (Kathayat et al 2018). While Kong et al (2013) concluded that there was a clear plasma membrane staining, they did not discuss the membrane-associated intracellular staining observed in their microscopy images, which, to our opinion, is not incompatible with a mitochondrial localization of their construct.…”
Section: Acyl Protein Thioesterasesmentioning
confidence: 95%
See 1 more Smart Citation
“…APT1 and APT2 were reported, and widely accepted, to display a cytosolic localization with preferred membrane association to the Golgi apparatus and the plasma membrane based on overexpression of fusion proteins using myc-FLAG (Kong et al 2013) or mCitrine (Vartak et al 2014) tags. We have, however, recently found that endogenous APT1 or APT1 overexpressed as a fusion to small tags localize primarily (although not exclusively) to mitochondria, whereas overexpression of APT1 using a bulky tag such as mCitrine prevents it from accumulating in mitochondria (Kathayat et al 2018). While Kong et al (2013) concluded that there was a clear plasma membrane staining, they did not discuss the membrane-associated intracellular staining observed in their microscopy images, which, to our opinion, is not incompatible with a mitochondrial localization of their construct.…”
Section: Acyl Protein Thioesterasesmentioning
confidence: 95%
“…While Kong et al (2013) concluded that there was a clear plasma membrane staining, they did not discuss the membrane-associated intracellular staining observed in their microscopy images, which, to our opinion, is not incompatible with a mitochondrial localization of their construct. APT2 does not display this sensitivity to tag size showing a broad distribution including the cytosol, the Golgi apparatus and the plasma membrane (Kong et al 2013;Vartak et al 2014;Kathayat et al 2018). Whereas APT1 has been included in the Mitocarta compendium as a potential mitochondrial protein (Pagliarini et al 2008;Calvo et al 2016), no clear mitochondrion-targeting sequence has been reported.…”
Section: Acyl Protein Thioesterasesmentioning
confidence: 99%
“…It has been recently shown that an active and dynamic S-depalmitoylation is present in mitochondria, regulating S-palmitoylation [52]. It is thus tempting to speculate that S-palmitoylation also occurs in the T. cruzi mitochondrion.…”
Section: Discussionmentioning
confidence: 99%
“…Daher kann sich das Abbilden der tatsächlichen subzellulären Verteilung der Enzymaktivität als schwierig herausstellen und Ergebnisse können leicht fehlinterpretiert werden. Eine Möglichkeit, die ungewünschte Diffusion aktivierter Sonden zu minimieren und dadurch die Genauigkeit der Lokalisierung der Enzymaktivität zu erhöhen, liegt darin, die Sonden in speziellen Organellen zu akkumulieren . Bei dieser Strategie wird jedoch davon ausgegangen, dass die Enzyme nur in gewissen Organellen aktiv sind und die Aktivität in anderen Organellen wird missachtet.…”
Section: Methodsunclassified